2017
DOI: 10.1534/g3.117.041848
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Recognition Motif-Containing Protein Functions in Meiotic Silencing by Unpaired DNA

Abstract: Meiotic silencing by unpaired DNA (MSUD) is a biological process that searches pairs of homologous chromosomes (homologs) for segments of DNA that are unpaired. Genes found within unpaired segments are silenced for the duration of meiosis. In this report, we describe the identification and characterization of Neurospora crassa sad-7, a gene that encodes a protein with an RNA recognition motif (RRM). Orthologs of sad-7 are found in a wide range of ascomycete fungi. In N. crassa, sad-7 is required for a fully ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(134 reference statements)
1
7
0
Order By: Relevance
“…ZML2 also plays a role in wound-induced lignification as a transcriptional repressor for the lignin biosynthesis in maize ( Velezbermudez et al, 2015 ). The RNA recognition motif-containing ( RRM ), one of the largest families of RNA binding proteins gene widely detected not only in plants and animals, but also in fungus, plays an important role in RNA recognition and editing ( Fetka et al, 2000 ; Rebay et al, 2000 ; Samarajeewa et al, 2017 ). In plants, as documented in model plants of Arabidopsis and maize, RRM is required for plastid and mitochondrial RNA editing ( Sun et al, 2013 ), and previous studies showed that an organelle RRM mutant exhibits slower growth and delayed flowering time ( Shi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…ZML2 also plays a role in wound-induced lignification as a transcriptional repressor for the lignin biosynthesis in maize ( Velezbermudez et al, 2015 ). The RNA recognition motif-containing ( RRM ), one of the largest families of RNA binding proteins gene widely detected not only in plants and animals, but also in fungus, plays an important role in RNA recognition and editing ( Fetka et al, 2000 ; Rebay et al, 2000 ; Samarajeewa et al, 2017 ). In plants, as documented in model plants of Arabidopsis and maize, RRM is required for plastid and mitochondrial RNA editing ( Sun et al, 2013 ), and previous studies showed that an organelle RRM mutant exhibits slower growth and delayed flowering time ( Shi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, none of the known MSUD proteins are essential for cell viability (Samarajeewa et al 2017). As demonstrated in Figure 3, if sad-8 is functional during the asexual stage (a speculation based on its expression profile), it is unlikely to be a crucial factor in growth and development, as the corresponding deletion strain is proficient in linear growth and conidial production.…”
Section: Sad-8 Is Not Required For Either Vegetative Growth or Sexualmentioning
confidence: 99%
“…SAD-2 is a scaffold protein responsible for bringing SAD-1 and others to the perinuclear region (Shiu et al 2006;Decker et al 2015). The precise functions of SAD-4, SAD-5, and SAD-7 are unclear, although the first two are necessary for siRNA biogenesis and the last one may coordinate nuclear and extranuclear silencing events (Hammond et al 2013a, b;Samarajeewa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The 6-day-old perithecia were fixed in a solution of 100 mM PIPES (pH 6.9), 10 mM EGTA, 5 mM MgSO4 and 4% paraformaldehyde for 20 minutes at room temperature as previously described (32). Perithecia were subsequently washed and stored in sodium phosphate buffer (80 mM Na2HPO4 + 20 mM NaH2PO4).…”
Section: Assaying Hh1-gfp Expressionmentioning
confidence: 99%